Prevalence of mental, behavioural or neurodevelopmental disorders according to the International Classification of Diseases 11: a scoping review protocol - Nafarieh, K; Krüger, S; Deutscher, K; Schreiter, S; Jung, A; Fazel, S; Heinz, A; Gutwinski, S (BMJ Publishing Group, 2024)
Introduction: Due to a change in diagnostic prerequisites and the inclusion of novel diagnostic entities, the implementation of the 11th revision of the International Classification of Diseases (ICD-11) will presumably change prevalence rates of specific mental, behavioural or neurodevelopmental disorders and result in an altered prevalence rate for this grouping overall. This scoping review aims to summarise the characteristics of primary studies examining the prevalence of mental, behavioural or neurodevelopmental disorders based on ICD-11 criteria. The knowledge attained through this review will primarily characterise the methodological approaches of this research field and additionally assist in deciding which psychiatric diagnoses are—given the current literature—most relevant for subsequent systematic reviews and meta-analyses intended to approximate the magnitude of prevalence rates while providing a first glimpse of the range of expected (differences in) prevalence rates in these conditions. Methods and analysis: MEDLINE, Embase, Web of Science and PsycINFO will be searched from 2011 to present without any language filters. This scoping review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review guidelines. We will consider (a) cross-sectional and longitudinal studies (b) focusing on the prevalence rates of mental, behavioural or neurodevelopmental disorders (c) using ICD-11 criteria for inclusion. The omission of (a) case numbers and sample size, (b) study period and period of data collection or (c) diagnostic procedures on full-text level is considered an exclusion criterion. This screening will be conducted by two reviewers independently from one another and a third reviewer will be consulted with disagreements. Data extraction and synthesis will focus on outlining methodological aspects. Ethics and dissemination: We intend to publish our review in a scientific journal. As the primary data are publicly available, we do not require research ethics approval.